Nonlinear association between triglyceride-glucose index and risk of hyperuricemia in early-stage cardiovascular-kidney-metabolic syndrome: a cross-sectional study of United States population - Chen, Xinyang; Liang, Yan (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveCardiovascular-kidney-metabolic (CKM) syndrome represents a critical intersection of cardiovascular, renal, and metabolic disorders, emphasizing the importance of early risk stratification and intervention. The triglyceride-glucose (TyG) index, a surrogate marker of insulin resistance, has shown promise in predicting cardiometabolic risk. However, its association with hyperuricemia in early-stage CKM syndrome remains uncertain.MethodsThis study analyzed data from 14,716 adult participants in the NHANES 2005–2018 dataset. A complex survey weight design and multiple imputation techniques were utilized to address missing data. The relationship between the TyG index and hyperuricemia was examined using generalized additive models and piecewise regression, with multivariable logistic regression adjusting for 14 potential confounders.ResultsThe TyG index demonstrated a significant positive association with hyperuricemia. Each unit increase in the TyG index was associated with a 62% higher risk of hyperuricemia (OR = 1.62, 95% CI: 1.45–1.81). A non-linear relationship was identified, with an inflection point at a TyG index of 9.50. Below this threshold, higher TyG index values were significantly associated with increased odds of hyperuricemia (OR = 2.18, 95% CI: 1.82–2.61), while above the threshold, the association became non-significant (OR = 0.79, 95% CI: 0.57–1.10). Subgroup analyses confirmed consistent associations across various demographic and clinical characteristics.ConclusionsThe TyG index may serve as a valuable biomarker for identifying hyperuricemia risk in individuals with early-stage CKM syndrome, offering potential utility in clinical and public health settings. Further longitudinal studies are warranted to confirm these findings and assess the impact of TyG index-guided interventions on CKM syndrome progression.